Shubayqa 6: a new Late Natufian and Pre-Pottery Neolithic A settlement in north-east Jordan. (December 2016) - Richter, Tobias; Arranz-Otaegui, Amaia; Boaretto, Elisabetta; Bocaege, Emmy; Estrup, Erin; Martinez-Gallardo, Cesar; Pantos, George Alexis; Pedersen, Patrick; Sæhle, Ingeborg; Yeomans, Lisa
Abstract : The Pre-Pottery Neolithic A (PPNA; c. 9600–8500 cal BC) period in the Levant provides the earliest confirmed evidence for plant cultivation anywhere in the world, marking a significant escalation in the human management of plants towards fully fledged agricultural food production. Until now, the majority of PPNA sites have been documented in the Jordan Valley, the Wadi Araba and farther north along the Upper Euphrates (e.g. Mureybet, Jerf el-Ahmar, Djade). By contrast, few PPNA sites have so far been reported from the semi-arid to arid eastern part of the Levantine interior. Among these is El Aoui Safa (Coqueugniot & Anderson1996 ) and sporadic flint scatters elsewhere in the Harra . Recent fieldwork in the Qa' Shubayqa area in the Harra has produced the first evidence for a more substantial settlement site in this region.